Penerapan RAD pada Aplikasi E-Learning Lembaga Bimbingan Belajar Gold Generation - nurhasan, usman; Mujahid, Muhammad; Sukmadewi, Ferina (Universitas Nusantara PGRI Kediri, 2021)
The development of information and technology has helped people to do their activity. In future living, information and technology will be the most dominant sector. Technology takes part in most of the aspects such education. Technology’s role is urgently needed, the example is Gold Generation Tutoring Agency as their service quality improvement. During this time tryout and tasks is done in a paper and not recorded on a database. It complicates the agency officers to manage the students’ grade and their tasks. And tutors find themselves in difficult situation in monitoring their students. Another popular name at the moment is E-Learning, it is one of learning process models that utilize media of information and technology communication especially internet. By the existence of e-learning that is directly connected to a database will ease the admin and the officers of the tutoring agency to manage the students grade and correct their task results, and not only for better service, but also for easing the students with lesson materials. According to the things mentioned above,